NEUTRINO DETECTORS AS PROBES OF MASSIVE COSMOLOGICAL RELICS - Sarkar, S (1992)
Underground detectors are sensitive to extraterrestrial high energy neutrinos such as those from the decays of massive metastable cosmological relic particles predicted by new physical theories. We find that present data from the IMB and Fréjus nucleon decay experiments, together with data from the Fly's Eye air shower array, already set stringent constraints. If particles of mass ∼ 1 - 1014 TeV constitute the cosmological dark matter then their lifetime is bounded to be greater than ∼ 1014 - 1018 yr. These limits probe interesting regions in the parameter space of superstring-motivated models and extended technicolour models. © 1992.